Corybas kaiganganianus (Orchidaceae), a new, rare helmet orchid from Samar Island, Philippines - Delos Angeles, Marjorie D.; Buot Jr., Inocencio E.; Moran, Cecilia B.; Robinson, Alastair S.; Tandang, Danilo N. (Phytotaxa, 2022)
Corybas Salisbury (1807: t. 83) comprises approximately 120 highly distinctive and diminutive terrestrial and lithophytic species widely distributed from India to the western Pacific (Pridgeon et al. 2001, Aldrich & Haggins 2008, Chung & Hsu 2008, Chantanaorrapint & Chantanaorrapint 2016, Govaerts et al. 2019). The Philippines has six Corybas species (Pelser et al., 2011): C. boholensis Tandang, Bustamante, Reyes & Lyon (2020a: 261), Bohol, Visayas;, C. circinatus Tandang & Bustamante (2020b: 135), central Palawan; C. geminigibbus Smith (1927: 13), Mt. Victoria, Palawan; C. laceratus Williams (1937: 54), Rizal Prov., Luzon; C. merrillii (Ames) Ames (1908: 42), Mt. Mariveles, Luzon; and C. ramosianus Dransfield in Dransfield et al. (1986: 611), Ilocos Norte Prov., Luzon. Corybas is often overlooked and understudied owing to its diminutive size and ephemeral flowers (Tandang et al. 2020a), and ongoing explorations of the Philippine Archipelago have demonstrated the merit of this observation, with several species having been newly documented and described in recent years from areas that are known to have been botanized in the past.